ESTIMATING MUD EXPULSION RATES FROM TEMPERATURE MEASUREMENTS ON HåKON MOSBY MUD VOLCANO, SW BARENTS SEA - Kaul N.; Heesemann M.; Foucher J.-P. (My University, 2006)
The Håkon Mosby Mud Volcano (HMMV), located on the Norwegian-Barents-Svalbard continental margin in 1250 m water depth, has been identified and described as a structure caused by upward transport of mud, pore water and gas [e.g. Eldholm, O., Sundvor, E., Vogt, P.R., Hjelstuen, B.O., Crane, K., Nilsen, A.K., Gladczenko, T.P., 1999. SW Barents Sea continental margin heat flow and Håkon Mosby Volcano. Geo-Marine Letters 19, 29-37]. During RV Polarstern expedition ARK XIX/3b in 2003, an integrated study took place to investigate the detailed morphology, biology, chemistry and geophysical aspects of HMMV [Klages, M., Thiede, J., Foucher, J.-P., 2004. The Expeditions ARK XIX 3a, 3b and 3c, Berichte zur Polarforschung, 488.]. In this paper, we describe a detailed survey involving more than 100 temperature gradient measurements in order to reveal the temperature structure of HMMV. Values of apparent heat flow up to 3000 mW/m2 and absolute temperatures up to 25.8 °C have been detected. These enormously high heat flux values do not reflect deep-seated thermal gradients but are a result of surface mud flows. The occurrence and abundance of mud flows varies in different areas within the HMMV inner crater. A combination of very shallow, ROV-derived temperature measurements, a large number of intermediate depth temperature gradients and nine deep penetrating gravity corers allows us to reconstruct the history of activity of HMMV. Modeling of the observed temperature gradients indicates vigorous activity with very recent mud flows. Furthermore, the supply of energy and material from the HMMV is estimated to have an annual mass volume of ~15,000 m3. From the thermal corona of HMMV and the observed horizontal heat flux, it is possible to deduce that the long term temperature of the mud pond is stable at a temperature approximately similar to the recent maximum temperature of 25 °C. © 2006 Elsevier B.V. All rights reserved.
Keywords: CONVECTION; HEAT FLOW; MUD VOLCANO; SEAFLOOR HYDROTHERMAL SYSTEM; SW BARENTS SEA